Application of Guidance and Counseling Media in Overcoming Learning Loss - Ni Made Diah Padmi; Sarmila Sarmila (Bisma The Journal of Counseling, 2021)
Guidance and Counseling is closely related to information. During the Covid-19 Pandemic, Guidance and Counseling services are carried out online and must be able to carry out services optimally. So that the process of delivering information can only be done online. In this case the BK teacher must think about how the service material can be delivered communicatively even though it is online. BK media is a means of delivering service material. Initially, the media became a means of supporting counseling guidance, but during the COVID-19 pandemic, the media became the main means of delivering service material with the aim of being better understood by students. The purpose of this study is to describe the skills of BK teachers in using guidance and counseling media in overcoming Learning Loss. The research method used is descriptive qualitative. Based on the research conducted, it was obtained an average score of 68 with high, medium and low categories. Of the 30 teachers who participated, 40% of them, namely 12 teachers, had a score below the average of 68.